Climate Change Impact on the Offshore Wind Energy Over the North Sea and the Irish Sea - Susini, Stefano; Menendez, Melisa; Eguia, Pablo; Blanco, Jesus Maria (Frontiers in Energy Research, 2022)
The impact of climate change on the environment and human activities is one of the biggest concerns for the international community. Wind energy represents one of the most reliable and promising technology to achieve the target reduction of emissions. Though more intense and uniform resources characterize offshore areas, climate change may alter the environmental conditions and thus Levelized Cost of Energy evaluation. In this study, we analyze the impact of climate change on the offshore wind energy sector over the North Sea and the Irish Sea, where the majority of the European investments are located. To this aim, seven regional climate model simulations from the EURO-Cordex project are first evaluated. The ERA5 reanalysis product is considered the historical reference information after its validation against in-situ records and it is used to analyze the climate simulations by assessing their performance to reproduce weather types. Several statistics are calculated to assess the skill of each model in reproducing past climatology for the reference period (1985-2004). Since no significant differences between simulations are highlighted, an ensemble of all the seven simulations is used to characterize future changes in the offshore climate. Weather types under the representative concentration path scenario RCP8.5 for the future period 2081-2100 are then analyzed to describe the changes in climatological mean and extreme events. Regional climate model simulations are bias-corrected by applying the empirical quantile mapping technique. Then, future changes in six wind energy climate indicators (i.e. mean and extreme wind speed, wind power density, operation hours, gross energy yield, and capacity factor) are estimated for seven operating offshore wind farms. Results indicate a slight decrease in wind energy production, particularly in the northwest of the domain of study, testified by a reduction of all the climate indicators. However, large uncertainties in the projected changes are found at the wind farms located close to the south coast of the North Sea. Extreme wind conditions show a modest rise in the southeastern part of the region, related to an increase of the weather types dominated by cyclonic systems off Scotland shores.